Preparedness and response for catastrophic disasters - Bissell, Rick (CRC Press/Taylor & Francis, 2013)
Based on a popular course for the FEMA Higher Education project, Preparedness and Response for Catastrophic Disasters provides important insight into plans to mitigate and respond to the devastation caused by large-scale catastrophic events. Hurricane Katrina provided clear evidence that these occurrences are both qualitatively and quantitatively different from other disasters. Recent tragedies, like the 2004 South Asia tsunami, the 2010 earthquake in Haiti, and the 2011 earthquake, tsunami, and resulting nuclear plant meltdown in Japan further illustrate that we are not prepared for such events